Modern bamboo structures : proceedings of First International Conference on Modern Bamboo Structures (ICBS-2007), Changsha, China, 28-30 October 2007 /: proceedings of First International Conference on Modern Bamboo Structures (ICBS-2007), Changsha, China, 28-30 October 2007. (©2008) - Unknown
No abstract available